Uṣūl al-Barajmātiyah fī Ḍaui al-‘Aqīdah al-Islāmiyah - Moh. Isom Mudin; Syamsul Hadi Untung (Universitas Darussalam Gontor, 2017)
Pragmatism is one of contemporary issues in Greek philosophy which was later developed by the number of modern figures such as William James, Webster and Charles Sender Pierce. Pragmatism is generally defined as a school of thought which considers everything based on every principle of benefit that it owned, knowledge for instance. Human seek the knowledge in order to make their life better. Due to the fact that pragmatism is built on the foundation that validity of an act and its value is evaluated from the advantages as its consequent, then everything shoul adhere to the principles. Pragmatism, in its progress, approves the harmony between the mind and human actions. Furthemore, the standard of absolute functions or benefits are referred back relatively to the subject. At this point, of we review the prgamatism from religion perspective, it could convey us to the relativism of truth. It can be concluded here that as an idelogy brought from the perspective of philosophy and religion, pragmatism should be strictly criticized from the view of Islam according to its negative implications toward religious understanding. This paper will try to elaborate on pragmatism chronologically, related to its contribution and relation toward Islamic Studies, expressing its principles associated with the perspectives of knowledge, akhlaq, and religiuos norms.